Effect of Weft Binding Structure on Compression Properties of Three-Dimensional Woven Spacer Fabrics and Composites - LIU Shengjie; JIANG Fei; ZENG Jinjin; SHAO Huiqi; JIANG Jinhua; CHEN Nanliang (东华大学学报（英文版）, 2023)
TS179; With the wide use of three-dimensional woven spacer composites(3DWSCs),the market expects greater mechanical properties from this material.By changing the weft fastening method of the traditional I-shape pile yarns,we designed three-dimensional woven spacer fabrics(3DWSFs)and 3DWSCs with the weft V-shape to improve the compression performance of traditional 3DWSFs.The effects of weft binding structures,V-pile densities,and V-shaped angle were investigated in this paper.It is found that the compression resistance of 3DWSFs with the weft V-shape is improved compared to that with the weft I-shape,the fabric height recovery rate is as high as 95.7%,and the average elastic recovery rate is 59.39%.When the interlayer pile yarn density is the same,the weft V-shaped and weft I-shaped 3DWSCs have similar flatwise pressure and edgewise pressure performance.The compression properties of the composite improve as the density of the V-pile yarns increases.The flatwise compression load decreases as the V-shaped angle decreases.When the V-shaped angle is 28° and 42°,the latitudinal V-shaped 3DWSCs perform exceptionally well in terms of anti-compression cushioning.The V-shaped weft binding method offers a novel approach to structural design of 3DWSCs.